Exploring the comorbidity mechanisms of ITGB2 in rheumatoid arthritis and membranous nephropathy through integrated bioinformatics analysis - Wenlong Cao; Yuqin Wang; Jing Xiong (Renal Failure, 2025)
Background Patients with rheumatoid arthritis (RA) are more likely to comorbid renal diseases, with membranous nephropathy (MN) being the most common. This study aimed to explore the common pathogenesis between RA and MN using integrated bioinformatics analysis.Methods Bulk and single-cell RNA sequencing datasets were obtained from the Gene Expression Omnibus and ImmPort databases. Differential expressed genes (DEGs) were identified and enrichment analysis was performed. Topology analysis and the random forest algorithm were applied to identify hub genes. The single-sample Gene Set Enrichment Analysis method was used to assess immune infiltration. Single-cell RNA sequencing analysis was employed to compare the transcript levels of key gene across different cell types. Pseudotime analysis was conducted using Monocle3, and cellular communication was analyzed with CellChat. The L1000FWD database was used to identify potential drugs, and molecular docking was performed.Results 66 common upregulated DEGs were identified, primarily associated with leukocyte migration and the chemokine signaling pathway. ITGB2 was finally identified as the shared pathogenic gene of both RA and MN. ITGB2 was predominantly expressed in macrophages, and its expression increased as M0 macrophages differentiated into M1 macrophages. BAFF signaling between macrophages with high ITGB2 expression and B cells/plasma cells was enhanced. Small molecules targeting ITGB2, including LY-294002 and CP466722, may serve as potential drugs for both RA and MN.Conclusion As the pathogenic gene shared by both RA and MN, ITGB2 may play a role in M1 macrophage polarization and contribute to the maturation and differentiation of B cells through BAFF signaling.